Morphological characterization of Badis species (Teleostei: Badidae) from Nepal - Blair, William K.; van Der Voort, Stefan; Edds, David R. (Zootaxa, 2018)
We characterized morphological variation among 172 specimens of Badis sp. (Teleostei: Badidae), collected from across Nepal and previously identified as Badis badis, to investigate whether any represented an undescribed species. Size-corrected principal component analysis (PCA), cluster analysis (CA), and discriminant analysis (DA) revealed four significantly different groups. One group was characterized by shallower body depth and shorter pelvic to anal distance than other groups and lacked a cleithral blotch. It was identified as Badis andrewraoi, previously unknown from Nepal, yet represented in our sample by 19 specimens from small rivers in the southeastern part of the country. Distribution of the remaining groups, all identified as B. badis, did not correspond to a zoogeographic hypothesis relating to major river drainages. Instead, morphological differences among these groups was better explained by allometric shifts. We provide information on the distribution and ecology of B. andrewraoi and B. badis in Nepal.